2021
DOI: 10.1101/2021.07.02.450858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genome-wide association study of serum proteins reveals shared loci with common diseases

Abstract: With the growing number of genetic association studies, the genotype-phenotype atlas has become increasingly more complex, yet the functional consequences of most disease associated alleles is not understood. The measurement of protein level variation in solid tissues and biofluids integrated with genetic variants offers a path to deeper functional insights. Here we present a large-scale proteogenomic study in 5,368 individuals, revealing 4,113 independent associations between genetic variants and 2,099 serum … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In two studies of 3301 and 5368 individuals, respectively, the same sentinel variant (rs2304058) was detected with an effect on circulating PDGFRB levels; each minor allele was associated with one standard deviation in plasma PDGFRB levels. 27,28 The effect of this common variant on the circulating proteins levels was independent of protein-altering, germ-line variants in PDGFRB. 27 PDGFRB expression is upregulated in lung tissue from PAH patients 12 and may be involved in the pharmacological effect of Imatinib on pulmonary vascular tissue; the IC 50 of Imatinib for PDGFRB is around 600 nM, 37 a concentration exceeded by trough plasma levels (averaging 700 ng.ml À1 ) in IMPRES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies of 3301 and 5368 individuals, respectively, the same sentinel variant (rs2304058) was detected with an effect on circulating PDGFRB levels; each minor allele was associated with one standard deviation in plasma PDGFRB levels. 27,28 The effect of this common variant on the circulating proteins levels was independent of protein-altering, germ-line variants in PDGFRB. 27 PDGFRB expression is upregulated in lung tissue from PAH patients 12 and may be involved in the pharmacological effect of Imatinib on pulmonary vascular tissue; the IC 50 of Imatinib for PDGFRB is around 600 nM, 37 a concentration exceeded by trough plasma levels (averaging 700 ng.ml À1 ) in IMPRES.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Of note here, three separate population-based studies have identified a cis-acting protein quantitative trait locus (pQTL) located close to PDGFRB, influencing circulating levels of PDGFRB, that reaches genome-wide significance. [26][27][28] If PDGFRB is an important target for Imatinib in PAH, common genetic variants influencing PDGFRB protein levels may affect therapeutic response, or at least the dose required to elicit a response, and the risk of dose-limiting adverse effects.…”
Section: Background and Rationalementioning
confidence: 99%
“…44 Specifically, rs10982156 and rs3762056 have been previously associated with coagulation factor X levels. 45 46 47 Recently, rs10982156 has also been associated with serum levels of tissue factor pathway inhibitor and serine protease inhibitor Kazal-type 2, 46 the latter being associated with stroke, 48 mean platelet volume, and platelet count, 49 among others. In addition, rs150611042 has been associated with thrombin generation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The human plasma proteome comprises an intricate network of proteins, either secreted or shed into the bloodstream, facilitating essential functions and intertissue communication. 7 Dysregulation of these proteins often signals disease, positioning them as crucial targets for pharmacological intervention. 8 Given the ease of blood collection compared to other tissues, circulating proteins offer a promising resource for identifying diseasespecific molecular signatures in large population cohorts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8 Given the ease of blood collection compared to other tissues, circulating proteins offer a promising resource for identifying diseasespecific molecular signatures in large population cohorts. 7 Advancements in proteomic methods now allow researchers to simultaneously quantify numerous circulating proteins in large-scale study populations. 9 Genome-wide association studies (GWAS) assessing the levels of these proteins facilitate the identification of protein quantitative trait loci (pQTLs), enhancing our understanding of the genetic architecture governing protein expression.…”
Section: ■ Introductionmentioning
confidence: 99%